Bariatric-Metabolic Surgery: A Promising Solution for Non-Alcoholic Steatohepatitis - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
Non-Alcoholic Steatohepatitis (NASH) is a growing global health concern, with significant implications for liver health and overall well-being. NASH is a condition characterized by inflammation and liver cell damage in individuals who have excess fat in their liver (steatosis) but no significant alcohol consumption.1,2 Treatment for NASH primarily focuses on managing underlying risk factors and promoting liver health. Addressing the complex nature of this disease requires a comprehensive understanding of treatment options.1,3,4 The current clinical management options include lifestyle modifications (healthy, balanced diet low in saturated fats/refined carbohydrates, regular exercise and maintaining a healthy weight), pharmacotherapy (Pioglitazone, semaglutide, Vitamin E, obeticholic acid, selonsertib and cenicriviroc), management of underlying conditions (obesity, type 2 diabetes and dyslipidaemia) and monitoring and treatment of complications (cirrhosis and hepatocellular carcinoma).